Managing English Young Learners’ Classroom Activities through Gestures: A Multimodal Perspective - Widia Yunita; Fuad Abdullah; Meli Mellan; Arini Nurul Hidayati; Havid Ardi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Managing classroom activities in children has become a challenge for English as a Foreign Language (EFL) teachers. Teachers usually use gestures in class activities, such as giving directions and pointing at students. This study explores the multimodal representation of the teacher's gestures when managing classroom activities in the EYL context. Data were collected through non-participant observation and analyzed by Systemic Functional Multimodal Discourse Analysis (SFMDA). The findings show that four meanings are multimodally represented in teacher gestures, namely (1) building student-teacher relationships through clapping and thumbs up, (2) emphasizing instruction through raising hands, pointing and lifting class objects, (3) encouraging involvement of students in academic tasks through finger pointing and counting down, and (4) warning of disruptive behavior of students through pulling gestures. Pedagogically, this research provides a paradigm shift that classroom-based communication does not have to use a single semiotic source but also a combination of other semiotic sources to help students understand teacher instructions easily.